A novel adhesive with exceptional underwater adhesion properties, capable of complete curing in aquatic environments - Chao Zhang; Rui Dou; Weiwei Xing; Qing Liu; Ling Cai; Wenrong Xia; Haowei Wu; Wenliang Fu; Donggang Xu (Journal of Materials Research and Technology)
Despite the challenges to the development of an underwater adhesive with strong and rapid properties, we innovatively proposed the use of tertiary amine groups to crosslink linear molecules containing urea groups, forming a mesh structure to achieve strong cohesion. Additionally, the formation of more high-energy crosslinks could enhance interfacial adhesion strength, resulting in the development of a novel adhesive that promised complete cure underwater with exceptional underwater adhesion properties. The tensile strength of this adhesive on an iron substrate was 8.07 MPa, which far surpassed commercially available adhesives used in the air. Atomic force microscopy measurements revealed microscopic adhesion forces up to 185.610 nN. Further studies demonstrated that the novel adhesive maintained excellent adhesion performance in saline solutions and at lower curing temperatures (0–10 °C), indicating promising applications in high-salinity, low-temperature aquatic environments. Moreover, the use of methyl propionate, a food-grade synthetic flavoring agent, as a reaction solvent not only provided hydrophobic protection, but also enhanced the safety of the adhesive, expanding its applications. This research presents a novel adhesive with strong underwater adhesion properties, with potential applications in high-salinity, low-temperature aquatic environments, thus offering new insights in this field.